2015
DOI: 10.6004/jadpro.2015.6.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders in the Oncology Patient

Abstract: Thyroid disease and cancer diagnoses are common conditions likely to coexist. Optimal management requires appropriate diagnostic testing and consideration of a number of factors, including overall health status and prognosis. Hypothyroidism and hyperthyroidism can lead to a number of symptoms that may affect not only quality of life but can interfere with the patient’s ability to tolerate cancer treatment. Imaging studies performed for cancer staging can identify incidental structural abnormalities in the thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
13
0
2
Order By: Relevance
“…However, one can surmise that chemotherapy might be a risk factor for thyroid disorders, since more than 12% of our study population developed hyperthyroidism (17 patients) or hypothyroidism (15 patients) during the course of cancer therapy. This assumption is in line with the findings of other trials [22,[26][27][28].There were also no changes of survival outcomes in correlation with the treatment of thyroid disorders.…”
Section: Discussionsupporting
confidence: 91%
“…However, one can surmise that chemotherapy might be a risk factor for thyroid disorders, since more than 12% of our study population developed hyperthyroidism (17 patients) or hypothyroidism (15 patients) during the course of cancer therapy. This assumption is in line with the findings of other trials [22,[26][27][28].There were also no changes of survival outcomes in correlation with the treatment of thyroid disorders.…”
Section: Discussionsupporting
confidence: 91%
“…rs13260246 maps to, and is an eQTL for, SLC26A7 , which functions as a Cl − /HCO 3 − exchanger and chloride channel, 32 and is expressed in several tissues including the thyroid. Chemotherapy can cause thyroid dysfunction and response to treatment may be affected by pre‐existing thyroid conditions 33‐35 . SLC26A7 is also expressed in parietal cells and genetic deletion results in decreased gastric acid secretion 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…While increased rates of incidental detection with more sensitive imaging tools and more frequent use of ultrasound could explain some of the incidence increase, we would also expect more sensitive imaging to detect other solid tumours, which we did not observe. Multiple studies have found positive associations between radiation therapy, but not chemotherapy (Meadows et al , ), and the risk for subsequent thyroid cancer after a diagnosis of head and neck cancer, AML, or HL (Ron et al , ; Meadows et al , ; Tolisano et al , ), and some studies have described thyroid disorders associated with rituximab use (Raterman et al , ; Hartmann, ). Our findings suggest that the increased risk of thyroid cancer post‐rituximab occurred in DLBCL patients with either localized/regional or advanced stage disease regardless of radiation therapy use.…”
Section: Discussionmentioning
confidence: 99%